Research Trends in E-tourism: A Bibliometric Analysis using VOSviewer - AWANG, Mesak Yamres (Integration: Journal Of Social Sciences And Culture, 2023)
Purpose: This study was conducted to determine (1) the growth of the number of scientific publications in the field of E-tourism, (2) the number of publications per field/subject, and (3) the map of publication development based on keywords and publication year.MethodologyThis study used a quantitative descriptive method with bibliometric analysis. Data was collected by searching through the Google Scholar database with the keyword "E-tourism" with the category "keywords for 2012–2022 using Publish or Perish 8 software. In addition, VOSviewer software is used to analyze the publication of development maps.FindingsThe study results show that the growth of scientific publications in land e-tourism shows fluctuations and an increasing trend. The highest increase will occur in 2022, with 41 documents (13.67%). Most subjects and subjects are in the fields of services, development, technology, and systems. While the keywords that appear the least are effort and challenge. The interrelationships between topics are grouped into eight clusters, seen through network visualization.ImplicationThis research is expected to assist researchers in determining themes to be researched and can also be a reference for tourism research.